Feasibility of sit training for patients with severe COVID-19 pneumonia during deep sedation: A case report. Issue 22 (4th June 2021) - Kinoshita, Tokio; Umemoto, Yasunori; Yasuoka, Yoshinori; Yoshikawa, Tatsuya; Kouda, Ken; Hori, Shinnosuke; Mikami, Yukio; Nishimura, Yukihide; Miyamoto, Kyohei; Kato, Seiya; Tajima, Fumihiro
Abstract: Rationale: There have been a few reports on the early rehabilitation of patients with coronavirus disease (COVID-19), and none on the effectiveness and adverse events of early mobilization for mechanical ventilation patients (other than COVID-19) during deep sedation. This report indicates that sitting without adverse events is possible in patients with severe COVID-19 pneumonia during deep sedation with muscle relaxation. Patient concerns: A 65-year-old man with a history of diabetes mellitus, lacunar infarction, and Parkinson's disease was admitted to a local hospital for pneumonia due to COVID-19. After admission, the patient was managed on a ventilator under deep sedation with muscle relaxants and sedatives. Twelve days after admission, the patient was transferred to our hospital due to his worsening respiratory status. Diagnosis: Pneumonia due to COVID-19 was diagnosed using a polymerase chain reaction–dependent method. Interventions: The day following transfer, a physical therapist started passive range of motion training and sitting. Outcomes: The period spanning his initial rehabilitation to muscle relaxant medication interruption was 9 days, and he underwent 7 rehabilitation sessions. The patient was unable to sit during only one of the 7 sessions due to pre-rehabilitation hypoxemia. In 5 of the 6 sitting sessions, PaO2/FiO2 transiently decreased but recovered by the time of subsequent blood sampling. The patient's PaCO2 decreased during all sessions. His blood pressure did not drastically decrease in any sitting session, except the first. Sputum excretion via sputum suction increased during sitting, and peak inspiratory pressure did not change. Lessons: The patient eventually died of pneumonia due to COVID-19. However, sitting during deep sedation with muscle relaxants did not cause any serious adverse events nor did it appear to cause obvious negative respiratory effects. Abstract : Supplemental Digital Content is available in the text